Further Investigation Into Detection Efficiency and False Alarm Rate for the Geostationary Lightning Mappers Aboard GOES‐16 and GOES‐17. Issue 2 (23rd February 2021) - Bateman, Monte; Mach, Douglas; Stock, Michael
Abstract: The Geostationary Lightning Mapper (GLM) is a geostationary lightning detection and location instrument, developed for the R generation of Geostationary Operational Environmental Satellites (GOES‐R, S, T, and U). This paper details a new technique to assess detection efficiency (DE) and false alarm rate (FAR), which indicate how well the instrument is detecting lightning and rejecting nonlightning. In an attempt to compare GLM with the best possible ground truth data, we clustered several ground‐based lightning networks into a single "virtual" network and compare it to the GLM results. A major issue with determining the GLM DE and FAR values is that over much of the instrument field of view (FOV), there are no high DE systems. To assess the GLM DE and FAR over these regions, we modified our prior coincidence criteria by increasing the time window from ±1 s to as much as ±10 min to account for the lower DE of the ground truth systems. Using the expanded time window, we compare GLM flash data from August 1, 2019 through January 31, 2020 for both instruments against the virtual network lightning flash data. We find that increasing the time window, while maintaining the distance criteria of 50 km, greatly improve the DE and FAR values. With the full ±10 min time window, over the whole GLM FOV, the GLMs on GOES‐16 and GOES‐17 have a DE of over 90%. For the same time window, the FAR for GLM on GOES‐16 is just over 5%, while the FAR for the GLM on GOES‐17 is just under 20%. Plain Language Summary: In order to evaluate the quality of the Geostationary Lightning Mapper (GLM) data, we need to compare it to other, well‐understood sources of lightning data. To account for the lack of high detection efficiency ground truth data over much of the viewing GLM area, we have increased the time window for comparisons to ±10 min. Using the larger time window, we find that the GLMs see as much as 90% of the lightning seen by other lightning detecting systems. Key Points: We present a new technique to calculate detection efficiency (DE) and false alarm rate (FAR) for the Geostationary Lightning Mappers (GLMs) on GOES‐16 and GOES‐17 by expanding the time coincidence window Using this new technique, the DE and FAR are actually much better than we have been previously able to show With more months of data, the GLM DE and FAR should improve in regions with very little lightning